The role of creative literature teaching based character on character development - Andri Noviadi; Sumiyadi Sumiyadi; Tedi Permadi (Universitas Mulawarman, 2023)
The purpose of this study was to investigate the effectiveness of character-based creative literature learning in developing student character which includes attitudes, behavior, and personality. The research method used was a quasi-experimental involving 250 high school students. The sample was selected using random sampling technique. The findings show that learning character-based creative literature makes a positive contribution to the development of student character, which includes attitudes, behavior, and student personality. The effect of learning literature on student character produces t values at the posttest stage for each aspect of attitude, behavior, and personality (4.452, 3.683, and 4.579) and p values less than 0.05. In addition, the effect size of character-based literary learning on character development is 5.80 which has a significant influence. So, it can be concluded that teaching character-based creative literature has a significant positive influence on character development (attitudes, behavior, and personality) in high school students. The implication of this research is that literature can be used as an alternative in instilling character in students.